A Multidisciplinary Perspective on Motor Impairment as an Early Behavioural Marker in Children with Autism Spectrum Disorder. (August 2016) - May, Tamara; McGinley, Jennifer; Murphy, Anna; Hinkley, Trina; Papadopoulos, Nicole; Williams, Katrina J; McGillivray, Jane; Enticott, Peter G; Leventer, Richard J; Rinehart, Nicole J
Abstract : Objectives: There is no medical test for autism spectrum disorder (ASD), a heterogeneous condition currently defined in the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM‐5) by dysfunction in social, communication, and behavioural dimensions. There is agreement in the literature that the motor profile of ASD may hold the key to improving clinical and diagnostic definition, with DSM‐5 now referring to motor deficits, including "odd gait" (p. 55), as part of the ASD clinical description. This review describes the history of motor impairment in ASD, types of motor problems, and age‐related motor findings and highlights evidence gaps and future research. Method: A narrative review is provided of the research literature describing motor impairment in ASD and its ability to differentiate between ASD versus non‐ASD cohorts. Results: Findings show differences in motor development in children with ASD from infancy onwards, including difficulties across motor coordination, arm movements, gait, and postural stability. Motor disturbance may appear in young children with ASD prior to social and language difficulties becoming clinically apparent. However, challenges remain in defining and measuring the early motor profile that is specific to ASD. Despite well‐established motor impairments in ASD, there is a lack of evidence regarding which motor‐based interventions will be effective in this group. Conclusions: Motor impairment holds promise as an early diagnostic sign, a behavioural marker, and a means by which to improve identification and possibly phenotypic delineation in ASD. Further research is required to determine whether motor abnormalities can sensitively differentiate ASD from other developmental conditions and to establish evidenced‐based interventions to reduce the associated impairment.